Synthesis of cyclic sulfoximines and their application in the expedient synthesis of cyclic sulfinamides and 3-pyrrolines - Ward, Jon-Paul (2019)
The synthesis of sulfoximines has been studied since the late 1940s but their application in academia and industry has only started to be exploited over the last 20 years. In 2013, a novel [2,3]-sigmatropic rearrangement of 2-vinylaziridines to cyclic sulfoximines (R2 = mesityl or tert-butyl) was discovered by the Stockman group. The first project investigates the de-tert-butylation of tert-butyl sulfoximines (R2 = tert-butyl) to afford the unprecedented chiral cyclic sulfinamides. This has enabled a two-step telescoped protocol to be developed, whereby chiral cyclic sulfinamides can be prepared from readily available tert-butyl sulfinimines. The second project revisits a previous finding within the Stockman group, which was the ring contraction of mesityl cyclic sulfoximines (R2 = mesityl). The scope of the existing [2,3]-sigmatropic rearrangement to afford mesityl cyclic sulfoximines is expanded. Subsequently, the scope of the novel ring contraction of mesityl cyclic sulfoximines to 3-pyrrolines in one step is greatly expanded. Finally, the third project concerns the further functionalisation of the cyclic sulfoximine and cyclic sulfinamide products, which were produced during the first and second projects. This small study is only an introduction into the potential of these novel three-dimensional structures.